CONGENITALLY MISSING SECOND PERMANENT MOLARS: CASE REPORTS - Aneta Munteanu; Cătălina Farcașiu; Arina Vinereanu; Alexandru-Titus Farcașiu; Horia-Octavian Manolea; Mihaela-Rodica Păuna; Ioana-Andreea Stanciu (Romanian Society of Oral Rehabilitation, 2022)
Congenital tooth absence is a common dental anomaly in humans. Congenital absence of second permanent molars (SPM) is determined by a number of complex interactions between genetic, epigenetic and environmental factors that intervene during the process of dental development. The prevalence of hypodontia in permanent teeth ranges from 4.4% to 13.4% depending on the continent. Among all missing teeth, the prevalence of SPM is very low (lower SPM - 1.8%, upper SPM - 1.5%). Because SPM agenesis is very rare and there are few studies related to this subject in the literature, the aim of the present study was to present five cases of missing SPM associated with the absence of other permanent posterior teeth are presented. Patients with agenesis of SPM showed a significantly disturbed development of their other SPMs. For all presented cases there was an association with the agenesis of the neighbouring third molar while for one case also a nearby premolar was missing. Even if SPM agenesis does not occur frequently, early diagnosis is very important in order to prevent impairment of masticatory function and occlusal dysfunctions.